Exocannabinoids effect on in vitro bovine oocyte maturation via activation of AKT and ERK1/2 (2016)
ABSTRACT : Endocannabinoids are known to mediate practically all reproductive events in mammals; however, little is known about their role in oocyte maturation. Through RT-PCR and immunocytochemistry, this study confirms the presence of CB1 and CB2 cannabinoid receptors in bovine oocytes and shows how exposure to the exogenous cannabinoids HU-210 and THC during their in vitro maturation (IVM) activates the phosphorylation of AKT and ERK1/2 proteins associated with the resumption of meiosis. Although supplementation with HU-210 or THC during IVM did not increase blastocyst yields, the expression of interferon tau (IFNτ) and gap junction alpha-1 protein (GJA1) was enhanced at the blastocyst stage. Our data suggest that cannabinoid agonists may be useful IVM supplements as their presence during oocyte maturation upregulates the expression in blastocysts of key genes for embryo quality.